Pengembangan Media Pembelajaran Keterampilan Menyimak Berbasis Online Menggunakan Google Form dan Google Classroom - Wisman Wisman; Rio Kurniawan (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
This study aims to develop online learning media for listening skill by using google form and google classroom which is tested in the course of listening skill for the first semester students. Type of the research used is Research & Development (R&D). The research instruments used were online developed tests, questionnaires, and expert validation sheets. The development used was the 4D development model (define, design, develop, and disseminate). At the disseminate stage it was not widely implemented because the product was only limited to students of the Indonesian Language Education Study Program, FKIP, Bengkulu University. The results showed that the development of online-based listening skills learning media using google form and google classroom was feasible for use by students of the Indonesian Language Education Study Program, Faculty of Teacher Training and Education, University of Bengkulu. This is indicated by the assessment based on the expert validation sheet at valid qualifications with an average of 4.00. The assessment based on the student response questionnaire is in very good qualification with an average of 3.22. Then, the assessment based on student test results is in good qualification with an average of 82.93.